2021
DOI: 10.12669/pjms.37.3.3348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olanzapine combined with risperidone in the treatment of schizophrenia and its influence on cognitive function

Abstract: Objective: To explore the effect of risperidone combined with olanzapine in the treatment of schizophrenia and its influence on cognitive function. Methods: Ninety-eight schizophrenic patients in our hospital who were admitted and treated between June 2018 and December 2019 were selected. The study group was treated with risperidone combined with olanzapine, and the control group was treated with risperidone. The clinical efficacy, Positive and Negative Syndrome Scale (PANSS) score, Wisconsin Card Sortin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The control group was treated with tandospirone citrate (Sichuan Creed Pharmaceutical Co., Ltd., approved by H20052328, 5 mg ∗ 24 capsules), 10 mg orally each time, 3 times a day. Insomniacs are allowed to take zolpidem before going to bed (Sanofi (Hangzhou) Pharmaceutical Co., Ltd., approved by Chinese medicine H20044989), and the dose is controlled at 5–10 mg/d [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…The control group was treated with tandospirone citrate (Sichuan Creed Pharmaceutical Co., Ltd., approved by H20052328, 5 mg ∗ 24 capsules), 10 mg orally each time, 3 times a day. Insomniacs are allowed to take zolpidem before going to bed (Sanofi (Hangzhou) Pharmaceutical Co., Ltd., approved by Chinese medicine H20044989), and the dose is controlled at 5–10 mg/d [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Relevant studies have shown that patients with schizophrenia have a certain degree of cognitive dysfunction or impairment. 20,21 In this study, the scores of trail making test in the observation group were significantly higher than those of the control group, while the scores of symbolic coding, verbal memory, maze, visual memory, and semantic fluency were significantly lower than those of the control group, indicating that the patients had a certain degree of cognitive dysfunction in the early stage of onset. Pearson correlation analysis showed that the levels of serum TNF-α and iNOS in the observation group were positively correlated with the trail making test scores, and negatively correlated with the scores of symbolic coding, verbal memory, maze, visual memory, and semantic fluency.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 51%
“…However, not all patients may respond similarly, and these treatments are not devoid of side effects. For instance, antipsychotics are linked with increased neurological and metabolic adverse effects in young patients 26 , 27 , though strategies exist to lessen these effects 20 , 27 . Hyperprolactinemia is a clinically significant adverse effect of risperidone treatment in both adults 28 , 29 and, putatively, adolescents 30 .…”
Section: Discussionmentioning
confidence: 99%
“…To further address these symptoms, Risperidone was initiated at 0.5 mg/day, with rapid increments of 0.5 mg every third day, targeting a dosage of 4 mg/day. Low-dose Olanzapine (5 mg) was also added, influenced by case studies suggesting that it can mitigate the common side effects of Risperidone and thereby enhance treatment tolerability 20 . During the titration phase for Risperidone, the patient experienced sedation and excessive daytime sleepiness, both of which fully resolved upon reaching the target dose.…”
Section: Patient 1 Navigating Complexities In Treatment-resistant Dep...mentioning
confidence: 99%